Nilai-Nilai Pendidikan Karakter dalam I Korintus 13:1-13 - Elkana, Samuel; Jaminter Ompusuggu; Joshua Christian Wenas; Tri Subekti; Yeyen Darmadi (Sekolah Tinggi Teologia Kerusso Indonesia, 2023)
Believers face challenges in educating the next generation of young people, in terms of forming and developing character. Character education is considered very important to be taught to believers from an early age because character education is a learning process to foster spiritual maturity in the form of Bible-based values, attitudes, and behaviors. The purpose of learning the values ​​of character education according to that is so that students have a mature personality in Christ. In 1 Corinthians 13:1-13 it describes love which has understanding and an explanation of character values. If the character is formed, it will greatly determine the character of the nation in the future. This research was conducted using qualitative methods or literature presented in the form of a biblical analysis of character education according to 1 Corinthians 13:1-13.